Legal Protection for Female workers in Indonesia (Study on the Rights of Female Workers in Tolitoli) - Mulyadi, Mulyadi; Yodo, Sutarman; Sulbana, Sulbana (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
The lack of guarantees for female workers' rights remains a significant issue in Tolitoli Regency, encompassing concerns such as equal pay, decent work, maternity leave, childbirth and breastfeeding rights, social security, and protection against discrimination. This study, using a socio-legal approach with both qualitative and quantitative methods, finds that labor laws protecting female workers have not been fully implemented. Specifically, 90.2% of companies fail to provide maternity leave, and many others do not adhere to all relevant labor regulations. Key obstacles include limited awareness of rights, weak legal enforcement, and gender discrimination, along with a lack of employer responsibility. The study suggests that the Manpower Law can help create a more conducive environment for the protection of female workers' rights.